Pregnancy Exercise on Childbirth Clinical Outcome - Shinta Novelia; Siti Syamsiah; Ira; Bunga Tiara Carolin (Health and Technology Journal (HTechJ), 2023)
Some of the problems that are quite often encountered by midwives during childbirth assistance are some complications during childbirth, including power problems, the mother's mistakes in the pushing process, and problems with improper breathing regulation which can cause a long labor process, so preventive measures can be increased such as pregnancy exercise which can show better clinical results or clinical outcomes at the time of delivery. This study aims to determine the effect of pregnancy exercise on clinical outcomes of childbirth at the Pratama Ratna Komala Clinic, Bekasi Regency, in 2022. This study used a non-parametric testing method with the Mann-Whitney method, totaling 20 respondents with 10 respondents participating in pregnancy exercise and 10 respondents did not participating in pregnancy exercise. The results of differences in clinical outcome between the experimental and control group showed that the Asymp Sig. (2-tailed) < 0.05 so that H0 was rejected which means that there is an effect of pregnancy exercise on clinical outcomes of childbirth. Pregnancy exercise can reduce pain and speed up the delivery process. It is hoped that the Pratama Ratna Komala Bekasi Clinic will continue to socialize pregnancy exercises to pregnant women to continue doing pregnancy exercises regularly. Midwives need to provide health counseling to pregnant women regarding the benefit of pregnancy exercise.